NUMERICAL STUDY OF THE EFFECT OF ROCK DISSOLUTION ON THE PORE STRUCTURE OF CARBONATE SAMPLES BASED ON EXPERIMENTAL DATA - Bolysbek Д.А.; Assilbekov Б.К.; Kuldjabekov А.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article studies the change in the pore structure of carbonate samples, consisting almost entirely of calcite, as a result of dissolution. For this purpose, 8 cubic sub-samples (#1-8) were selected from 4 cylindrical carbonate samples (I, II, III and IV), which were tested during laboratory experiments on pumping 12% and 18% hydrochloric acid solutions. Acid solutions were pumped at a flow rate of 4 and 8 ml/min, respectively. The pore structure of sub-samples was obtained using the Avizo software based on 2D X-Ray tomography images with a resolution of 19 μm. The characteristics of sub-samples were calculated by pore-scale simulation of water flow. A significant change in the pore structure indicated in sub-sample #3 with low initial porosity (8.7%) for which permeability increased 65 times its initial value. It was found that in sub-samples #1, 3 and 4, for which the mean pore and throat radii increased by more than 10%, there was a significant increase in permeability (2.5-65 times). On the contrary, 3% changes in the mean pore and throat radii of sub-sample #2 led to an increase in its permeability by only 25%. Rock dissolution significantly affected the pore size distribution. The results of this study can be useful for assessing the increase in reservoir permeability when stimulating the oil flow to the well by injecting acid solutions and the capacity and transport capabilities of carbonates during CO2 injection.